Ultrasound in the Assessment of Parotid Duct Stenosis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Journal of Ultrasound in Medicine, 2019)
Objectives Parotid duct stenosis may occur with or without accompanying ductal anomalies, with associated differences in their pathogenesis and management. By identifying the characteristics of a stenosis, ultrasound (US) can assist in tailored management of parotid duct stenosis. The objective of this study was therefore to describe the US characteristics of parotid duct stenoses and to evaluate criteria for whether and in what ways these can be distinguished from each other by using US. Methods A total of 108 patients who presented with parotid duct stenoses (130 parotid glands) were examined with high-resolution US between 2014 and 2017. The stenoses were assessed for duct dilatation, location, signs of ductal anomalies (circular encroachments/webs, duct bending/kinking, and presence of a megaduct) and the echogenicity of the gland parenchyma. Results Ultrasound was able to distinguish between stenoses associated with ductal anomalies and those without anomalies. Webs (82.5% versus 7.8%; P < .001), kinking (75.0% versus 3.3%; P < .001), and a megaduct (87.50% versus 15.63%; P < .001) and a tendency toward normal echogenicity in the gland parenchyma (77.5% versus 25.6%; P < .001) were significantly associated with ductal anomalies. Stenoses associated with ductal anomalies also had significantly larger duct diameters in comparison with those without anomalies (mean +/- SD, 9.19 +/- 3.65 versus 3.27 +/- 2.17 mm; P < .001). Conclusions This study describes US parameters that allow more detailed characterization of parotid stenoses with or without accompanying ductal anomalies. Differentiating between these at an early stage may be helpful for decision making on the further management in these patients.
CRIS-Team WoS Importer:2019-11-01